A case report of unexplained jejunal telangiectasia complicated with bleeding. (2020) - Zhang, Wen-jun; Huang, You-shan; Zhu, Zheng-ming; Luo, Hong-liang
Highlights: Jejunal telangiectasia with bleeding is relatively rare in clinic. The main clinical manifestation of small intestinal telangiectasia is hematochezia. This disease is prone to recurrent bleeding. There is a lack of specific and effective diagnostic methods in clinical. We gave some experience and suggestions in the process of surgical treatment. Abstract: Introduction: Small intestinal telangiectasia is a clinically rare disease, which is mainly characterized by gastrointestinal bleeding. There is a lack of specific and effective diagnostic methods in clinical practice due to its unknown etiology and difficult localization, it is often difficult to find the location of the lesion even through observation, touch, endoscope or intestinal incision. Case presentation: A 39-year-old female patient, who had black stool twice without obvious inducement 3 days ago, and came to our hospital for treatment and was hospitalized with gastrointestinal bleeding. the main manifestation of this patient was repeated black stool, sometimes dark red. Initially, we considered other diseases of the digestive tract (gastric ulcers, duodenal ulcers and intestinal tumors). However, no abnormalities were found by CT, gastroscopy and enteroscopy. Later, we considered that there was a greater possibility of intestinal vascular disease, and then blood clots was found in the upper and middle segment of the jejunum through capsule endoscopy, but no bleeding site was found. Therefore, we decided to open the abdomen for further intraoperative enteroscopy exploration, finally found the bleeding point, and then stopped the bleeding by suture. Later, through further follow-up, no rebleeding was found in the patient. Conclusion: Jejunal telangiectasia with bleeding is a very rare intestinal vascular disease, which is difficult to identify and diagnose clinically. Therefore, the possibility of this disease should be considered in patients with negative results through some examinations such as gastroscopy, enteroscopy, gastrointestinal barium meal radiography, etc. In order to treat in time and prevent bleeding